Dimensions of Sufistic Da’wah KH. Musta’in Ramly (1931-1985) - Mustain, Mustain; Budiantoro, Wahyu (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aimed to identify and explain the dimensions of KH's Sufistic da'wah. Musta'in Ramly. The research was conducted through historical and contextual excavations regarding his work in preaching. In particular, the study is directed at the Sufistic dimension of Musta'in Ramly. The research was conducted with a qualitative approach. Reviewing and documenting the book of Tsamratul Fikriyyah became the primary source of study and contextualized its work at several social levels of society. The results of this study indicate the dimensions of the Sufistic da'wah of KH. Musta'in Ramly uses two sizes, namely remembrance and thought. The remembrance dimension raises a guide in the form of a guidebook for istghotsah charity. Meanwhile, the dimension of thought functions to permanently activate the power of reason and rationality. He realized this by becoming the leader (Chancellor) of Darul 'Ulum University and being active in social, political, and religious activities.